Penerapan Teknik Phrasering dalam Kwartet Vokal dengan Lagu Time To Say Goodbye Bagi Mahasiswa Minat Vokal Program Studi Pendidikan Musik Universitas Katolik Widya Mandira Kupang - Kefi, Anggela Jeane (Universitas Jambi, 2025)
Phrasing technique is a crucial aspect in vokal performance, used to divide, organize, and interpret musical phrases to enhance clarity, expression, and meaning. In singing practice, common challenges include a lack of understanding of vokal techniques, especially in breath control and phrase connection. This study aims to introduce and apply the phrasing technique systematically to improve students’ vokal abilities, particularly in a vokal quartet format which requires harmony, collaboration, and strong musical interpretation. The research problems addressed are: (1) How is the phrasing technique applied in a vokal quartet? and (2) What are its impacts on vokal-interest students in the Music Education Study Program at UNWIRA Kupang? This research employed a descriptive qualitative approach with field action. Data were collected through literature review and direct observation. The application process was divided into three stages: the initial stage (recruitment of participants), the core stage (implementation of phrasing techniques), and the final stage (recording of the final performance). Students were trained in phrase division, breathing exercises, and the development of musical interpretation. The results show a significantly positive impact on the students’ singing skills, particularly in breath control and musical phrase connection. Although challenges such as reaching high notes and pitch accuracy were encountered, overall, the students were able to apply the technique well. This study contributes to the development of vokal teaching methods, especially in vokal quartet settings, and serves as a reference for improving vokal practice, teaching materials, and the musical competence of students in the Music Education Study Program at UNWIRA Kupang.